Análise temporal da relação entre o tremor fisiológico cinético e o envelhecimento com base em desenhos digitalizados da espiral de Arquimedes - Almeida, Maria Fernanda Soares de (2011)
Tremor is the most common movement disorder characterized by repetitive and stereotyped movements, and the elderly is the most affected population. The movement caused by tremor can be associated to many factors such as neurological disorders and natural processes. The latter is often referred to as physiological tremor and is present in greater or lesser degree, in all humans. The presence of severe tremor disorders causes many difficulties, and can indicate even the presence of diseases related to central nervous system. However, the dividing landmark between physiological tremor and that resultant of dysfunctions is tenuous and has not been precisely established. Thousands of people each year, begin to present some type of motor dysfunction, which interferes in their daily activities and reduces significantly the quality of life of these individuals. Most investigations on tremor attempt to understand its relation to neuromuscular dysfunctions. Therefore, there is a lack of studies that aim to investigate the complex relation between the physiological tremor and ageing, especially in kinetic conditions. In this context, the main motivation of this research was to quantify and analyse age-related changes in the kinetic tremor of clinically healthy individuals. For this, a number of features extracted from tremor activity, obtained from digitized drawings of Archimedes spirals, were analysed. In total, 59 subjects participated in the experiments. These individuals were divided into seven groups according to their ages and three types of analysis were carried out. First, the tremor activity was investigated by means of traditional features commonly used in tremor analysis, and secondly, Linear Discriminant Analysis (LDA) was employed for the study of the correlation between age and tremor. Finally, experimental nonlinear time series features were employed, such as state space reconstruction and estimation of Lyapunov exponents. The results obtained through the LDA showed significant statistical differences between the kinetic tremor activity of the young and elderly groups. Furthermore, it was found that LDA allowed for the estimate of a unique feature, so-called LDA-value, which showed to be linearly correlated with age.